POTENSI SUSU KEDELAI ASAM (SOYGURT) KAYA BIOAKTIF PEPTIDA SEBAGAI ANTIMIKROBA - Nirmagustina, Dwi Eva; Wirawati, Chandra Utami (Jurnal Penelitian Pertanian Terapan, 2014)
The research objective was to get the starter type and the fermentation time to produce soygurt that have a high peptide bioactive that functions as an antimicrobial. The study was conducted in a complete randomized block design with two replicates. The first factor is the starter types, which consists of 3 levels, 2 market starter (cimory and king yogurt) and 1 mixed starter. The second factor is the fermentation times, which consists of 3 levels, 9 hours, 12 hours, and 15 hours. The data obtained were analyzed by analysis of variance to get various error estimators and tests of significance by Duncan's test further to determine whether there is a difference between treatments. Two market starter (cimory and king yogurt) and 1 mixed starter did not produce peptide bioactive compounds . It is suspected microbes contained in the market starter cimory (S.thermophilus and L.delbrueckii ssp . Bulgaricus ), the market starter king yogurt (L.bulgaricus) and mixed starter (S.thermophilus and L.bulgaricus) did not produce peptide bioactive compounds. The inhibition effect of the test bacteria (E. coli and S. aureus) occurs due to the production of lactic acid and hydrogen peroxide during the fermentation process . The greatest inhibition shown by soygurt of the market starter cimory with a reduced number of cells in both types of test bacteria (E. coli and S. aureus) at 6 and 5 log cycles . Mixed starter has the lowest pH and the highest total acid than the marker starter cimory and king yoghurt. The starter types and the fermentation times were no significant effect on total dissolved solids of soygurt. The levels protein of soygurt, respectively 1.38 %, 1.48 %, and 1.68 (cimory, king yogurt, and mixed starter), while the fat content of soygurt 1.04%, 1.28 %, and 1.58% (cimory, mixed starter, king yoghurt) Keyword: soygurt, peptide bioactive, antimicrobe